2014
DOI: 10.17722/ijme.v3i1.118
|View full text |Cite
|
Sign up to set email alerts
|

The Connection between Self concept (Actual self Congruence & Ideal Self congruence) on Brand Preferences

Abstract: Abstract-This

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 70 publications
0
4
0
1
Order By: Relevance
“…Those traits by which one understands himself are considered steady properties. The actual-social self, on the other hand, is defined as “how people believe they are seen by significant others” (Hakimian et al, 2014 ) and is characterized by prevention-focused (non-losses) behavior that ensures safety and security (Higgins, 1996 , 1997 ; Toyama, 2022 ). The ideal self is sometimes referred to as the “desired self” or “idealized image” and is described as how people would like to perceive themselves (Sirgy, 1982 ; Hong and Zinkhan, 1995 ; Hakimian et al, 2014 ).…”
Section: Background and Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Those traits by which one understands himself are considered steady properties. The actual-social self, on the other hand, is defined as “how people believe they are seen by significant others” (Hakimian et al, 2014 ) and is characterized by prevention-focused (non-losses) behavior that ensures safety and security (Higgins, 1996 , 1997 ; Toyama, 2022 ). The ideal self is sometimes referred to as the “desired self” or “idealized image” and is described as how people would like to perceive themselves (Sirgy, 1982 ; Hong and Zinkhan, 1995 ; Hakimian et al, 2014 ).…”
Section: Background and Related Workmentioning
confidence: 99%
“…The actual-social self, on the other hand, is defined as “how people believe they are seen by significant others” (Hakimian et al, 2014 ) and is characterized by prevention-focused (non-losses) behavior that ensures safety and security (Higgins, 1996 , 1997 ; Toyama, 2022 ). The ideal self is sometimes referred to as the “desired self” or “idealized image” and is described as how people would like to perceive themselves (Sirgy, 1982 ; Hong and Zinkhan, 1995 ; Hakimian et al, 2014 ). In the consumption process, consumers seek to integrate their desired traits into their ideal self (Mathews, 2015 ; Dib and Johnson, 2019 ) and have more variety-seeking behaviors to satisfy their need for intense stimulation (Menon and Kahn, 1995 ).…”
Section: Background and Related Workmentioning
confidence: 99%
“…Faktor individu mempengaruhi seseorang dalam pembentukan harga diri. Penampilan fisik serta ciri-ciri yang tidak sesuai dengan kemauan atau ideal diri seorang akan menentukan baik atau buruknya harga diri orang tersebut (Upamannyu et al, 2014). Pembentukan harga diri juga dipengaruhi oleh faktor sosial yaitu teman sebaya dan lingkungan.…”
Section: Pendahuluanunclassified
“…The personality can affect the preference [21], [22]. Furthermore, these studies from various researchers suggest that preferences are related to self-concept [23]. Many researchers used the concept of participation in their studies and found the importance of cooperating among community, professionals, and the administration to exchange information about user's demand and what can be done with available resources.…”
Section: Theoretical Frameworkmentioning
confidence: 99%